Lipoprotein lipase in plasma after an oral fat load: relation to free fatty acids. - Karpe, F; Olivecrona, T; Walldius, G; Hamsten, A (1992)
Lipoprotein lipase (LPL) releases fatty acids from triglyceride-rich lipoproteins for use in cellular metabolic reactions. How this hydrolysis, which occurs at the vascular endothelium, is regulated is poorly understood. A fatty acid feedback system has been proposed by which accumulation of fatty acids impedes LPL-catalyzed hydrolysis and dissociates the enzyme from its endothelial binding sites. We examined this hypothesis in humans who were subjected to an oral fat tolerance test of a mixed-meal type. Plasma triglycerides, free fatty acids, and LPL activity were measured before and repeatedly during a 12-h period after intake of the fat load. Since soybean oil with a high content of linoleic fatty acid was the source of triglycerides, a distinction could be made between endogenous free fatty acids (FFA) and FFA derived directly from lipolysis of postprandial triglyceride-rich lipoproteins. Mean LPL activity was almost doubled (P less than 0.01) 6 h after intake of the oral fat load. The rise in LPL activity was accompanied by an increase of plasma triglycerides and linoleic free fatty acids (18:2 FFA), but not of total plasma FFA, which instead displayed a heterogeneous pattern with essentially unchanged mean levels. The postprandial response of LPL activity largely paralleled the postprandial responses of 18:2 FFA and triglycerides. The highest degree of parallelism was seen between postprandial 18:2 FFA and LPL activity levels. Furthermore, the integrated response (area under the curve, AUC) for plasma measurements of LPL correlated with the AUC for 18:2 FFA (r = 0.40, P less than 0.05), but not with the AUC for plasma triglycerides (r = 0.21, ns). The high degree of parallelism and significant correlation between postprandial plasma LPL activity and 18:2 FFA support the hypothesis of fatty acid control of endothelial LPL during physiological conditions in humans.